Economic evaluation of physical activity mass media campaigns across the globe: a systematic review - Marina B. Pinheiro; Kirsten Howard; Cathie Sherrington; Adrian Bauman; Nathalia Costa; Ben J. Smith; William Bellew; Ding Ding; Anne Tiedemann; Belinda Wang; Andreia C Santos; Fiona Bull; et al. (International Journal of Behavioral Nutrition and Physical Activity, 2022)
Abstract Background Physical activity mass media campaigns can deliver physical activity messages to many people, but it remains unclear whether they offer good value for money. We aimed to investigate the cost-effectiveness, cost-utility, and costs of physical activity mass media campaigns. Methods A search for economic evaluations (trial- or model-based) and costing studies of physical activity mass media campaigns was performed in six electronic databases (June/2021). The authors reviewed studies independently. A GRADE style rating was used to assess the overall certainty of each modelled economic evaluation. Results were summarised via narrative synthesis. Results Twenty-five studies (five model-based economic evaluations and 20 costing studies) were included, and all were conducted in high-income countries except for one costing study that was conducted in a middle-income country. The methods and assumptions used in the model-based analyses were highly heterogeneous and the results varied, ranging from the intervention being more effective and less costly (dominant) in two models to an incremental cost of US$130,740 (2020 base year) per QALY gained. The level of certainty of the models ranged from very low (n = 2) to low (n = 3). Overall, intervention costs were poorly reported. Conclusions There are few economic evaluations of physical activity mass media campaigns available. The level of certainty of the models was judged to be very low to low, indicating that we have very little to little confidence that the results are reliable for decision making. Therefore, it remains unclear to what extent physical activity mass media campaigns offer good value for money. Future economic evaluations should consider selecting appropriate and comprehensive measures of campaign effectiveness, clearly report the assumptions of the models and fully explore the impact of assumptions in the results. Review registration https://bit.ly/3tKSBZ3